2015
DOI: 10.1371/journal.pone.0145475
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Light Responses May Explain Vertical Distribution of Hymenophyllaceae Species in a Temperate Rainforest of Southern Chile

Abstract: Some epiphytic Hymenophyllaceae are restricted to lower parts of the host (<60 cm; 10–100 μmol photons m-2 s-1) in a secondary forest of Southern Chile; other species occupy the whole host height (≥10 m; max PPFD >1000 μmol photons m-2 s-1). Our aim was to study the photosynthetic light responses of two Hymenophyllaceae species in relation to their contrasting distribution. We determined light tolerance of Hymenoglossum cruentum and Hymenophyllum dentatum by measuring gas exchange, PSI and PSII light energy pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
4
24
0
Order By: Relevance
“…Filmy ferns have only one cell layer, and thus, their photosynthetic capacity is generally low, between ca. 1–4 μmol m −2 s −1 (Parra et al, ; Parra et al, ) as was also observed in the current study in fully hydrated samples (Table , Figure ). Due to lack of stomata and water‐permeable cuticular layer, the RWC of filmy ferns rapidly decreases in dry atmospheres, resulting in concomitant reductions in foliage photosynthetic characteristics (Flores‐Bavestrello et al, ; Proctor, ; Saldaña et al, ) as observed in our study (Figure , Table ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Filmy ferns have only one cell layer, and thus, their photosynthetic capacity is generally low, between ca. 1–4 μmol m −2 s −1 (Parra et al, ; Parra et al, ) as was also observed in the current study in fully hydrated samples (Table , Figure ). Due to lack of stomata and water‐permeable cuticular layer, the RWC of filmy ferns rapidly decreases in dry atmospheres, resulting in concomitant reductions in foliage photosynthetic characteristics (Flores‐Bavestrello et al, ; Proctor, ; Saldaña et al, ) as observed in our study (Figure , Table ).…”
Section: Discussionsupporting
confidence: 90%
“…We suggest that the LOX emissions during the desiccation primarily reflect the oxidative burst generated upon transfer of ferns from lower light/high humidity atmosphere to higher light/lower humidity atmosphere and associated generation of oxidative stress due to a certain overexcitation of photosynthetic machinery. In fact, low light/high humidity to high light/low humidity transitions are common during high intensity lighflecks and result in a large share of excess quantum flux density that can lead to photoinhibition of filmy ferns (Parra et al, ). Rapid responses to altered light and humidity conditions are consistent with previous observations of induction of LOX emission responses by higher light level (Loreto, Barta, Brilli, & Nogues, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies with Hymenophyllaceae species have shown valuable empirical evidence of an evolutionary shift of adaptive strategy from typical vascular plant adaptation to the poikilohydry most typical of bryophytes (Proctor et al 2012, Parra et al 2015, we are far from understanding the family or its diversity and Chile is one of the best places in the world to begin (Michael Proctor pers. comm.).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mosses of the genus Polytrichum , which have at least partially functional hydroids (i.e. a ‘pseudovascular’ system) present the largest A area and g m determined among bryophytes (Carriquí et al ., ) while, by contrast, ferns of the Hymenophyllaceae family, which have through evolution lost stomata and functionality of the vascular system, present moss‐like low photosynthesis rates (Parra et al ., ). In this sense, the already mentioned source/sink balance should also be considered as improving the source capacity (photosynthesis) may require larger sinks.…”
Section: Key Role Of Mesophyll Conductance and Other Physiological Trmentioning
confidence: 97%